Piperacillin Steady State Concentrations in Target Tissues Relevant for PJI Treatment-A Randomized Porcine Microdialysis Study Comparing Continuous Infusion with Intermittent Short-Term Infusion - Hans Christian Rasmussen; Pelle Hanberg; Martin Knudsen; Sara Kousgaard Tøstesen; Andrea René Jørgensen; Elisabeth Krogsgaard Petersen; Kristina Öbrink-Hansen; Kjeld Søballe; Maiken Stilling; Mats Bue (MDPI AG, 2023)
(1) Introduction: Piperacillin is a common antibiotic choice in the treatment of periprosthetic joint infections (PJI) caused by Pseudomonas aeruginosa. The aim of this study was to assess and compare the time with free piperacillin concentration above the minimum inhibitory concentration (fT > MIC) at steady state in target tissues relevant for PJI treatment following continuous and intermittent short-term infusion. (2) Methods: 16 pigs were randomized to receive either continuous or intermittent short-term infusion of piperacillin. Steady state piperacillin concentrations were assessed using microdialysis in tibial cortical bone, tibial cancellous bone, synovial fluid of the knee joint, and subcutaneous tissue. MIC-targets of 4, 8, 16, and 64 mg/L were applied. Plasma samples were obtained as reference. (3) Results: Continuous infusion resulted in longer fT > MIC for MIC targets of 4 mg/L and 8 mg/L compared to intermittent short-term infusion in all compartments with the exception of tibial cortical bone. For the MIC-target of 16 mg/L, continuous infusion resulted in a longer fT > MIC in all compartments except for the bone compartments. No differences between groups were seen when applying a MIC-target of 64 mg/L. (4) Conclusions: An aggressive dosing strategy may be necessary to obtain sufficient piperacillin concentrations in all bone compartments, particularly if more aggressive targets are applied. Based on the present study, continuous infusion should be considered in the treatment of PJI.